2017
DOI: 10.1080/20548923.2017.1361629
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the metaproteome: variability of protein preservation in ancient dental calculus

Abstract: Proteomic analysis of dental calculus is emerging as a powerful tool for disease and dietary characterisation of archaeological populations. To better understand the variability in protein results from dental calculus, we analysed 21 samples from three Roman-period populations to compare: 1) the quantity of extracted protein; 2) the number of mass spectral queries; and 3) the number of peptide spectral matches and protein identifications. We found little correlation between the quantity of calculus analysed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 70 publications
6
48
0
Order By: Relevance
“…Proteins were successfully recovered from all 10 of the dental calculus samples analysed, with total protein identifications ranging from 15 to 128 (following quality filtering) ( Table S5). The identified proteins were assigned primarily to the human proteome and to microbial taxa commonly found within the oral microbiome, as well as to common contaminants identified in previous dental calculus proteomic analyses (principally trypsin, human keratins and human collagens) (Hendy et al 2018a;Mackie et al 2017;Warinner et al 2014b) (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins were successfully recovered from all 10 of the dental calculus samples analysed, with total protein identifications ranging from 15 to 128 (following quality filtering) ( Table S5). The identified proteins were assigned primarily to the human proteome and to microbial taxa commonly found within the oral microbiome, as well as to common contaminants identified in previous dental calculus proteomic analyses (principally trypsin, human keratins and human collagens) (Hendy et al 2018a;Mackie et al 2017;Warinner et al 2014b) (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent developments in high‐throughput, high‐resolution, mass spectrometry have led to greatly improved sensitivity and accuracy, which have now begun to be applied in the field of palaeopathology. For example, shotgun mass spectrometry has been used to identify highly antigenic proteins associated with bacteria such as gingipains in medieval human dental calculus, periodontic disease‐associated bacteria in Roman period dental calculus, establish the possible presence of Mycobacterium through buccal swabs of a 500‐year‐old Inca mummy, the possibility of infection in 360‐year‐old bone samples from Tokyo using a label‐free approach, and identification of proteins associated with tissue inflammation in skin samples of ≈4200‐year‐old mummies from Egypt . In the only other exploration of the endogenous dental paleoproteome to our knowledge, peptides associated with plague bacterium Yersinia pestis were able to be identified in 300‐year‐old dental pulp from a funeral site in France …”
Section: Introductionmentioning
confidence: 99%
“…Often calculus preserves microfossils (Arensburg, ; Hardy et al, ; Henry and Piperno, ; Henry, Brooks, & Piperno, ; Lalueza Fox et al, ; Lazzati et al, ; Li et al, ; Radini et al, ; Wesolowski, Ferraz Mendonça de Souza, Reinhard, & Ceccantini, ; Zhang et al, ), chemical elements (Poulson et al, ; Price, Keenleyside, & Schwarcz, ) and biomolecules (Warinner et al, ). More specific studies have identified the use of fire in enclosed environments by presence of micro‐charcoal inclusions (Hardy et al, ), source of drinking water (Dudgeon and Tromp, ), pathogenic microorganisms (Mackie et al, ; Preus, Marvik, Selvig, & Bennike, ; Warinner et al, ), medicinal plants (Hardy et al, ), processed food (Buckley, Usai, Jakob, Radini, & Hardy, ; Henry, Brooks, & Piperno, ; Warinner et al, ), use of tobacco (Eerkens et al, ) and mtDNA (Black, Kerr, Henebry‐DeLeon, & Lorenz, ). For plant fibers, Blatt, Redmond, Cassman, & Sciulli () report the presence of archaeobotanical material ( Gossypium sp.)…”
Section: Introductionmentioning
confidence: 99%